To Improve Is to Change? The Effects of Risk Rating 2.0 on Flood Insurance Demand - Francesc Ortega; Ivan Petkov (Institute of Labor Economics (IZA), 2024)
We present a theory of the demand for flood insurance and empirically analyze the effects of the adoption of Risk Rating 2.0, using individual insurance histories for all NFIP policies. The reform increased exit and reduced entry, both in the flood zone and its periphery. The reform had highly heterogeneous effects on insurance costs and triggered adjustments in coverage and deductibles. On average, RR2 increased costs for renewers outside of the flood zone but lowered them for renewers in the flood zone, resulting in an overall average increase. However, the reform reduced revenue and increased financial exposure to flood risk.
Keywords: R11; R30; Q54; G22; 330; flood risk; insurance; Risk Rating 2.0; FEMA; NFIP